2022
DOI: 10.1007/s11418-022-01605-6
|View full text |Cite
|
Sign up to set email alerts
|

Lateral flow immunoassay for small-molecules detection in phytoproducts: a review

Abstract: Phytoproducts are involved in various fields of industry. Small-molecule (Mw < 900 Da) organic compounds can be used to indicate the quality of plant samples in the perspective of efficacy by measuring the necessary secondary metabolites and in the perspective of safety by measuring the adulterant level of toxic compounds. The development of reliable detection methods for these compounds in such a complicated matrix is challenging. The lateral flow immunoassay (LFA) is one of the immunoassays well-known for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 132 publications
0
18
0
Order By: Relevance
“…The sensitivity of competitive immunoassays can be enhanced by utilising a small amount of primary antibodies because competitive analytes at low concentrations can completely bind the primary antibodies. 27 As the amount of the antibodies coupled with AuNPs was increased, the antigen accessibility decreased because of the steric interference among antibodies. 19 In case of sandwich ICA, the use of bigger AuNPs and higher concentrations of mAb improved the sensitivity 28 because it increased the amount of AuNP-mAb that can associate with the test zone.…”
Section: Effect Of Aunp Particle Size and Mab-12g11 Amount On Icamentioning
confidence: 99%
“…The sensitivity of competitive immunoassays can be enhanced by utilising a small amount of primary antibodies because competitive analytes at low concentrations can completely bind the primary antibodies. 27 As the amount of the antibodies coupled with AuNPs was increased, the antigen accessibility decreased because of the steric interference among antibodies. 19 In case of sandwich ICA, the use of bigger AuNPs and higher concentrations of mAb improved the sensitivity 28 because it increased the amount of AuNP-mAb that can associate with the test zone.…”
Section: Effect Of Aunp Particle Size and Mab-12g11 Amount On Icamentioning
confidence: 99%
“…Xia et al have previously reported that sample volume can affect flow rate and that there is an inverse relationship between the effective concentration of analyte in the sample and the square of the change in flow rate [42,43]. Consequently, a larger volume may result in a lower effective antibody concentration as the flow rate of the analyte increases [43]. Therefore, 5-10 µL is the recommended volume and 15 min is the optimal time to obtain reproducible results.…”
Section: Monitoring the Antibody Against Sars-cov-2mentioning
confidence: 99%
“…Both viral antigens in nasopharyngeal swabs and specific antibodies in the blood can be easily and rapidly detected. Besides large proteins, such as viral antigens and antibodies, the LFIA also qualifies for the detection of small molecules, such as phytoproducts, mycotoxins, and pesticides [ 40 , 41 , 42 , 43 ]. An LFIA for the direct detection of CHLP based on colloidal gold detection has been developed previously [ 44 ].…”
Section: Introductionmentioning
confidence: 99%